Study of the Relationship Between Spectral Reflectivity and Water Quality Index in Hilla River - M. Kadhum Al-Bayati, Zahraa; H.Nayle, Israa; S. Jasim, Basheer (International Journal of Engineering and Technology, 2018)
The overall objective of this study was to use field spectro-radiometers for finding possible spectral regions for some physical and chemical parameters, The study area was divided into 20 stations on part of the Euphrates River, in Hilla city taking samples and studying the physical and chemical parameters and compared them with the standard specifications parameters:( Ph, TSS, E.C, T.D.S, CL) to calculate water quality indicators (for irrigation purposes) and a spectral reflectivity measurements to find the necessary the relationship of the reflectivity and water quality analysis. A GIS data base was conducted for mapping ,documenting and analyzing the Resources of pollution and water quality within the area of study, then Comparison of the spectral, bands of, the field S,pectro-radiometer, with those of the Landsat 8 depicted that are suitable spectral regions for monitoring water quality. Based on the results from this study and by, matching. the spectral, bands of the field spectro-radiometer with those of the Landsat 8 satellite sensor (or any other antenuptial), it has been found that suitable spectral regions for monitoring water quality in water treatment reservoirs are the following: Ph., EC and CL, at  the spectral range of (0.851–0.87) μm and (2.107–2.294) μm (TM, band5 and band 6), TSS, , TUR, at  the spectral region of (0.533–0.590) μm (TM, band 3), and for TDS, the region,(1.566–1.561) μm (TM, bands 6).